KNOWLEDGE AND PARTICIPATION OF UIR BIOLOGY AND MATHEMATICS EDUCATION STUDENTS ABOUT THE USE OF FOOD PACKING PLASTIC AS A SOURCE OF ENVIRONMENTAL POLLUTION - S Suryanti; S Sudarmi; Afnilafitra Dini (Jurnal Pelita Pendidikan, 2021)
This study aims to determine the knowledge and participation of biology education students and UIR mathematics education students regarding the use of plastic food wrap as a source of environmental pollution. The research was conducted in March-May 2021. The research method is a survey method. Data collection techniques using tests, questionnaires, interviews, and documentation. The instrument used is a test based on Bloom's taxonomy with 15 questions and a questionnaire of 20 statements, instrument testing, and reliability testing. The population in this study amounted to 243 students and used a saturated sample. The results showed that the average knowledge of UIR biology and mathematics education students about the use of plastic food wrap as a source of environmental pollution was 70.36% in the good category. Meanwhile, the participation of UIR biology and mathematics education students regarding the use of plastic food wrap as a source of environmental pollution with a value of 84.57% in the very good category. It can be concluded that the knowledge and participation of UIR biology and mathematics education students regarding the use of plastic food wrap as a source of environmental pollution are in a good category